Pharmacological inhibition of microsomal prostaglandin E synthase-1 suppresses epidermal growth factor receptor-mediated tumor growth and angiogenesis. - Federica Finetti; Erika Terzuoli; Elena Bocci; Isabella Coletta; Lorenzo Polenzani; Giorgina Mangano; Maria Alessandra Alisi; Nicola Cazzolla; Antonio Giachetti; Marina Ziche; Sandra Donnini (PLoS ONE, 2012)
Blockade of Prostaglandin (PG) E(2) production via deletion of microsomal Prostaglandin E synthase-1 (mPGES-1) gene reduces tumor cell proliferation in vitro and in vivo on xenograft tumors. So far the therapeutic potential of the pharmacological inhibition of mPGES-1 has not been elucidated. PGE(2) promotes epithelial tumor progression via multiple signaling pathways including the epidermal growth factor receptor (EGFR) signaling pathway.Here we evaluated the antitumor activity of AF3485, a compound of a novel family of human mPGES-1 inhibitors, in vitro and in vivo, in mice bearing human A431 xenografts overexpressing EGFR. Treatment of the human cell line A431 with interleukin-1beta (IL-1β) increased mPGES-1 expression, PGE(2) production and induced EGFR phosphorylation, and vascular endothelial growth factor (VEGF) and fibroblast growth factor-2 (FGF-2) expression. AF3485 reduced PGE(2) production, both in quiescent and in cells stimulated by IL-1β. AF3485 abolished IL-1β-induced activation of the EGFR, decreasing VEGF and FGF-2 expression, and tumor-mediated endothelial tube formation. In vivo, in A431 xenograft, AF3485, administered sub-chronically, decreased tumor growth, an effect related to inhibition of EGFR signalling, and to tumor microvessel rarefaction. In fact, we observed a decrease of EGFR phosphorylation, and VEGF and FGF-2 expression in tumours explanted from treated mice.Our work demonstrates that the pharmacological inhibition of mPGES-1 reduces squamous carcinoma growth by suppressing PGE(2) mediated-EGFR signalling and by impairing tumor associated angiogenesis. These results underscore the potential of mPGES-1 inhibitors as agents capable of controlling tumor growth.